Experiences in case mix implementation: a case study. (4th April 2005) - Barnes, Stuart J.
The health sector, being information-intensive, has tremendous potential for harnessing the power of information systems (IS). However, ironically, it is also one of the late-comers to the information-revolution. Only in the last two decades have UK hospitals started to become heavy investors in IS, led by Government initiatives to provide overarching information infrastructure and to make public sector organisations more accountable. One of these was the Resource Management Initiative, accompanied by the Case Mix IS – an organisation-wide system to provide clinical and management audit. Case Mix experiences in UK hospitals have typically been poorly documented, and those that have, paint a grim picture. This paper focuses on a detailed qualitative case study of a UK hospital that had relative success in implementation. As such, it provides a number of lessons learnt for other hospitals embarking on similar projects.